A pilot randomised trial of community-based care following discharge from hospital with a recent spinal cord injury in Bangladesh. (June 2017) - Hossain, MS; Harvey, LA; Rahman, MA; Bowden, JL; Islam, MS; Taylor, V; Muldoon, S; Herbert, RD
Objectives: To explore the feasibility of conducting a full trial designed to determine the effectiveness of a model of community-based care for people with spinal cord injury in Bangladesh. Study Design: A pilot randomised trial. Setting: Community, Bangladesh. Subjects: Participants were 30 people with recent spinal cord injury who were wheelchair-dependent and soon to be discharged from hospital. Intervention: Participants randomised to the intervention group received a package of care involving regular telephone contact and three home visits over two years. Participants randomised to the control group received usual care consisting of a telephone call and an optional home visit. Main measures: Participants were assessed at baseline and two years after randomization. The primary outcome was mortality and secondary outcomes were measures of complications, depression, participation and quality of life. Results: A total of 24 participants had a complete spinal cord injury and six participants had an incomplete spinal cord injury. Median (interquartile) age and time since injury at baseline were 31 years (24 to 36) and 7 months (4 to 13), respectively. Two participants, one in each group, died. Five participants had pressure ulcers at two years. There were no notable impediments to the conduct of the trial and no significant protocol violations. The phone calls and home visits were delivered according to the protocol 87% and 100% of the time, respectively. Follow-up data were 99% complete. Conclusion: This pilot trial demonstrates the feasibility of a full clinical trial of 410 participants, which has recently commenced. Sponsorship: University of Sydney, Australia.